2021
DOI: 10.1111/bjh.17116
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2‐induced remission of Hodgkin lymphoma

Abstract: SARS-CoV-2-induced remission of Hodgkin lymphoma A 61-year-old man was referred to the haematology department with progressive lymphadenopathy and weight loss. He was receiving haemodialysis for end-stage renal failure secondary to IgA nephropathy. He had been off immunosuppressive therapy for three years after a failed renal transplant. Needle-core biopsy of a supraclavicular node demonstrated Epstein-Barr virus (EBV)-positive classical Hodgkin lymphoma [EBV viral polymerase chain reaction (PCR) 4800 copies/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 1 publication
3
100
0
4
Order By: Relevance
“…Parvez et al considered that further rigorous genetic and molecular studies would update treatment and preventive strategies for recently emerged variants [ 131 ]. Additionally, Challenor et al reported a case in which an EBV-positive Hodgkin lymphoma patient was diagnosed with COVID-19 4 months later, palpable lymphadenopathy was reduced, and a PET/CT scan showed widespread resolution of the lymphadenopathy and reduced metabolic uptake throughout [ 132 ]. Challenor et al hypothesized that COVID-19 infection triggered an anti-tumour immune response and assumed that the mechanisms for this included cross-reactivity of pathogen-specific T cells with tumour antigens and the activation of natural killer cells by inflammatory cytokines produced by infection [ 132 ].…”
Section: Ebv Co-infectious Agentsmentioning
confidence: 99%
“…Parvez et al considered that further rigorous genetic and molecular studies would update treatment and preventive strategies for recently emerged variants [ 131 ]. Additionally, Challenor et al reported a case in which an EBV-positive Hodgkin lymphoma patient was diagnosed with COVID-19 4 months later, palpable lymphadenopathy was reduced, and a PET/CT scan showed widespread resolution of the lymphadenopathy and reduced metabolic uptake throughout [ 132 ]. Challenor et al hypothesized that COVID-19 infection triggered an anti-tumour immune response and assumed that the mechanisms for this included cross-reactivity of pathogen-specific T cells with tumour antigens and the activation of natural killer cells by inflammatory cytokines produced by infection [ 132 ].…”
Section: Ebv Co-infectious Agentsmentioning
confidence: 99%
“…Thus, chemotherapy and radiotherapy should be safe treatments for the cancer patient recovered from COVID-19. Interestingly, there is also a report that anti-SARS-CoV-2 antibody triggered the anti-tumor immune response in a Hodgkin's lymphoma patient 13 . Therefore, the protective role of IgG antibodies against SARS-CoV-2 in the cancer patient is not only important for them to prevent virus infection, but maybe also bene cial for the cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there have also been a few reports of COVID-19 being beneficial to lymphoma patients, presumably due to an “immunostimulatory effect”. Challenor and Tucker[ 33 ] reported the case of a 61-year-old man who went into remission after SARS-CoV-2 infection without treatment. Sollini et al [ 34 ] also report a case of a patient with follicular lymphoma, who having achieved a partial remission after bendamustine-based therapy, went onto achieve a complete remission after asymptomatic COVID-19.…”
Section: Impact Of Covid-19 By Lymphoma Subtypementioning
confidence: 99%